Effect of gamma-ray, electron-beam, and X-ray irradiation on antioxidant activity of mugwort extracts. (September 2021) - Hwang, Ko-Eun; Ham, Youn-Kyung; Song, Dong-Heon; Kim, Hyun-Wook; Lee, Mi-Ai; Jeong, Jong-Yeon; Choi, Yun-Sang
Abstract: The objective of this study was to compare the effect of radiation sources (gamma-rays, electron-beams, and X-rays) and dose levels (0, 2, 6, and 10 kGy) on the phytochemical profile of mugwort extracts. As the irradiation dose increased, antioxidant contents (total phenol and flavonoid contents) and antioxidant activities (DPPH radical scavenging activity, ferric reducing power ability, and nitrite scavenging capacity) increased, irrespective of the radiation source used. Interactions effects between the irradiation source and dose level in all the experiments of mugwort extracts were observed ( P  < 0.05), except for the nitrite scavenging capacity. Notably, gamma-ray irradiation led to an effective increase in not only the antioxidant contents but also the activities of mugwort extracts, followed by X-ray and electron-beam irradiation at doses up to 10 kGy ( P  < 0.05). Our findings suggest that the optimum irradiation source for boosting the physiological activity of mugwort extracts is gamma-rays. Therefore, enhanced activities of mugwort extracts through irradiation could be applied to various industries, especially as a natural antioxidant source in foodstuffs. Highlights: The effect of radiation sources on the antioxidant activity of mugwort was studied. Optimum irradiation source for boosting the physiological activity of mugwort extracts is gamma rays. Enhanced activities of mugwort extracts through irradiation could be applied. Irradiated mugwort had natural antioxidant source in foodstuffs.